1970
DOI: 10.33736/bjrst.249.2013
|View full text |Cite
|
Sign up to set email alerts
|

Notes on the Herpetofauna of Kampung Giam, Padawan, Sarawak

Abstract: Padawan lies at one of the proposed Sarawak Geopark, yet information on the herpetofauna of the area islimited. A survey was conducted from 16 August 2008 to 24 August 2008 to determine species assemblage andrelative abundance of herpetofauna at Kampung Giam, Padawan. Sampling involved stream and forest transects,quadrat, pitfall and sticky traps at four study sites along Sungai Sewa. A total of 13 species of frogs (62individuals), eight species of lizards (nine individuals) and four species of snake (one indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Likely due to the overlapping characteristics between these species, C. quadrivirgatus has been recorded from Sarawak (Das, 2004, 2006; Zainudin et al, 2013), although a recent study indicated that the individuals were likely a color morph of the C. pubisulcus complex (Davis et al, 2020). We show additional support for C. quadrivirgatus being distantly related from all Bornean congeners (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Likely due to the overlapping characteristics between these species, C. quadrivirgatus has been recorded from Sarawak (Das, 2004, 2006; Zainudin et al, 2013), although a recent study indicated that the individuals were likely a color morph of the C. pubisulcus complex (Davis et al, 2020). We show additional support for C. quadrivirgatus being distantly related from all Bornean congeners (Figure 4).…”
Section: Discussionmentioning
confidence: 99%